Environmental Flows Assessment for Macroinvertebrates at the River Reach Scale in Different Degrees of Hydromorphological Alteration - Szałkiewicz, Ewelina; Kałuża, Tomasz; Grygoruk, Mateusz (Frontiers in Environmental Science, 2022)
One of the most commonly used methods of environmental flows assessment is the approach based on Habitat Suitability Modeling (HSM) and habitat preferences curves (HPCs). Relationships between organisms and physical parameters describing the habitat remain strongly nonlinear and vary depending on several factors. The most common comparisons concern analyses between natural and regulated rivers, where the degree of river channel alterations is undefined and usually refers to all forms of hydromorphological degradation. Additionally, spatial scale and computational range of such a research mostly focus on longer river reaches and statistical analysis of HPC transferability, without detailed estimation of environmental flows values. The main aim of our research was assessment and comparison of environmental flows’ values for macroinvertebrates at two reaches of one river with different degrees of hydromorphological alteration. Two research hypotheses were verified: (1) morphological conditions impact on values of environmental flows and weighted usable area; (2) the mean value of environmental flows at the regulated river reach is higher compared to the natural reach. In order to put the obtained values of environmental flows into a broader context, the analyses of hydrological data and calculation of hydrology-based environmental flows were performed. Additionally, before determination of environmental flows, the transferability of habitat suitability criteria between reaches was verified. The obtained results confirmed research hypotheses, revealing strong dependence of environmental flows values to morphological conditions. Additionally, for both studied sections the lower limits of environmental flows were greater than hydrology-based values.